Molecular markers of Chloroquine resistance in India and Southeast Asia: A narrative review - Maskeri, Rakshita; Jain, Animesh; Ullal, Sheetal D (Indian Journal of Community Health, 2021)
Malaria is a major global public health problem mainly in the tropics and subtropics. Malaria control and elimination strategies mainly rely on efficacious antimalarial drugs. At present the major hurdle faced by malaria control programs is the drug resistance to antimalarials. Molecular surveillance using genetic markers associated with resistance provides a valuable tool for detecting and tracking resistance as well as providing an in-depth understanding of the development and spread of resistance. Despite numerous published literatures there are limited review articles on molecular markers of drug resistance. Hence a review was planned. An exhaustive literature search was performed on PUBMED using “malaria”, “resistance”, “molecular”, “antimalarial”, “Chloroquine”, “Pfcrt”, “Pfmdr”, “Pvcrt”, “Pvmdr”as key words. Data pertaining to India and Southeast Asia were included. This review showed the widespread presence of molecular markers of drug resistance in Plasmodium falciparum and development of resistance in Plasmodium vivax over the years in Southeast Asia and India. This can have implications on malaria elimination and treatment guidelines in this region.